Social Innovation - Nicholls, Alex; Dees, J. Gregory (International Encyclopedia of the Social & Behavioral Sciences (Second Edition), 2015)
Social innovation refers to the processes and outcomes that develop a novel approach to addressing a social problem or need. Compared to commercial innovation, it poses some distinctive challenges, particularly with regard to the incentives to invest in it, assessment of performance, and diffusion of effective innovations. Scholars began paying attention to this phenomenon in the late twentieth century, but many open research questions remain. The term ‘social innovation’ has had two meanings in the academic literature. In its earliest scholarly uses, primarily in sociology, it was used to refer to the creation of new patterns of human interaction, new social structures, or new social relations. The second focuses on innovations designed to address a social or environmental issue or to meet a specific social market failure or need. Often, both types of innovation are combined to establish new patterns of social relations that have positive social outcomes.
Keywords: Entrepreneuriat social; Ouvrages de référence; Réservé UdeM; Sciences sociales